Could N‐acetylcysteine improve the safety of clozapine? - Chrétien, Basile; Fédrizzi, Sophie; Lelong‐Boulouard, Véronique; Sassier, Marion; Alexandre, Joachim; Dolladille, Charles (Human Psychopharmacology Clinical and Experimental, 2020)
Clozapine is an atypical antipsychotic indicated in patients with treatment-resistant schizophrenia which remains underused due to safety issues. Mechanisms behind these adverse effects are complex and not fully understood. They may involve immune-related mechanisms, direct toxic effects and oxidative stress. Clozapine-induced oxidative stress might indeed notably be involved in the onset of neutropenia, agranulocytosis, myocarditis, sialorrhea, and metabolic alterations. Therefore, the association of N-acetylcysteine (NAC), an easily accessible, low-cost and well tolerated antioxidant drug could be of interest in clozapine-treated patients to improve clozapine safety. Furthermore, according to recent studies NAC could help to improve schizophrenia symptoms. We believe that the use of NAC in the context of clozapine prescribing merits further study, as it could improve clozapine safety which may lead to a wider use and ultimately improve the healthcare of thousands of patients. NAC could also secondarily show positive knock-on effects for the patients by improving clinical symptoms of schizophrenia in synergy with clozapine, and by reducing substance abuse and thus by improving the patient's overall condition. However, given the rarity of clozapine-induced severe adverse effects, only a large volume of data (e.g., National adverse events monitoring) could assess the benefits of NAC on clozapine safety.